QUESTIONING FOREIGN LANGUAGE LEARNING IN ISLAMIC PRE-SCHOOL - Indah, Rohmani Nur (Laboratorium Informasi & Publikasi Fakultas Humaniora UIN Maulana Malik Ibrahim Malang, 2010)
This paper questions the urgency of foreign language learning at early age by covering some arguments on the acquisition and bilingualism. Nowadays in Indonesia, under the interest of education, bilingual learning is undertaken by adopting the theory of bilingual acquisition referring to Chomsky’s ideas. In fact, the foreign language learning is not always in line with the principle of language acquisition especially for the early age children. The globalization era requires foreign language mastery so that for many institutions of children education have got the bilingual learning. As the example, some of Islamic educational institutions at the level of playgroup have applied the instruction in English and teaching Arabic words, by considering that the earlier foreign language learning is the better, and the fact that the golden age of brain development occurs at the first five years. This needs to be analyzed further, because there is also important task to have mother tongue language acquisition. For the community of multilingual such as in Indonesia, the acquisition of many languages is unavoidable. Therefore, parents are faced with two choices: To prior the mother tongue and bahasa Indonesia as second language or encourage the bilingual learning of Arabic and English.